Supralapsarianism reconsidered: Jonathan Edwards and the Reformed tradition - Hussey, Phillip A. (T & T Clark studies in systematic theology, 2024)
"This incisive book directly tackles the scholarship of Jonathan Edwards and interrogates the relationship between Christ and the decree within Reformed Theology. In doing so, it reveals the contemporary theological significance of supralapsarian Christology"--